2020
DOI: 10.1016/j.ijrobp.2020.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Understanding High-Dose, Ultra-High Dose Rate, and Spatially Fractionated Radiation Therapy

Abstract: While the workshop was co-sponsored by the NCI and RSS, the comments in this report are strictly the opinions of the co-authors and does not constitute endorsement of these results and/or treatments by the NCI and RSS or consensus of all the co-authors on each of the points. This report is designed to stimulate further formal research and development to explore the future clinical application of these novel therapies and not for implementation into routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 72 publications
0
80
0
2
Order By: Relevance
“…Since its early inception over 100 years ago by Kohler (1)(2)(3)(4), spatially fractionated radiation therapy (SFRT) in the form of 2D GRID has been applied clinically, although not as a mainstream radiation therapy modality. While conducting systemic clinical trials has been practically difficult, the reported clinical data have suggested favorable outcomes and clinical value of GRID therapy for the treatment of advanced bulky tumors (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). A recent workshop sponsored by the National Cancer Institute (NCI) and Radiosurgery Society (RSS) for assessment of, and discussion on, the techniques and clinical merits of SFRT resulted in a comprehensive summary report (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its early inception over 100 years ago by Kohler (1)(2)(3)(4), spatially fractionated radiation therapy (SFRT) in the form of 2D GRID has been applied clinically, although not as a mainstream radiation therapy modality. While conducting systemic clinical trials has been practically difficult, the reported clinical data have suggested favorable outcomes and clinical value of GRID therapy for the treatment of advanced bulky tumors (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). A recent workshop sponsored by the National Cancer Institute (NCI) and Radiosurgery Society (RSS) for assessment of, and discussion on, the techniques and clinical merits of SFRT resulted in a comprehensive summary report (6).…”
Section: Introductionmentioning
confidence: 99%
“…While conducting systemic clinical trials has been practically difficult, the reported clinical data have suggested favorable outcomes and clinical value of GRID therapy for the treatment of advanced bulky tumors (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). A recent workshop sponsored by the National Cancer Institute (NCI) and Radiosurgery Society (RSS) for assessment of, and discussion on, the techniques and clinical merits of SFRT resulted in a comprehensive summary report (6). The physical 2D GRID blocks or apertures, evolving from the early kV X-ray delivery systems to the modern-day megavoltage accelerators, with the same intention of normal tissue sparing, generate similar patterns of peak-to-valley dose distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Non-conventional radiotherapeutic techniques, such as FLASH, are now in clinical focus in order to design pioneering, biologically based clinical trials [57].…”
Section: Clinical Advantages Of Flash Radiotherapy Derived From Currementioning
confidence: 99%
“…Degrees of freedom that need to be optimized are the radiation dose, the fractionation schedule, radiation type, geometry of the irradiation field(s), irradiation angles, antibody type, drug concentration and drug delivery schedule. This also includes exhibiting the role of emerging radiation therapy modalities such as FLASH or spatial fractionation, which may also spare the blood pool efficiently, but for which the interaction with the immune system is unclear at the moment ( 91 ).…”
Section: Future Perspectivesmentioning
confidence: 99%